The roles of health literacy in parents' honey use and the use of complementary alternative medicine in a Turkish population - Suzan Tek Ayaz (BMC, 2023)
Abstract Background As a biologically based therapy, honey is used by parents in many parts of the world as a home remedy for their children. While information exists regarding the traditional use of honey for health issues in children, data regarding its relationship with health literacy is lacking. The aims of this study were to determine the use of honey to address children's health issues among parents of children aged 0-72 months and to explore the relationship between the use of complementary and alternative medicine (CAM) and health literacy. Methods The data for this descriptive, cross-sectional study were collected between October and November 2022 via an online survey of 907 parents of children aged 0-72 months. A sociodemographic data collection form, the Holistic Complementary and Alternative Medicine Questionnaire (HCAMQ), and the Turkey Health Literacy Scale-32 (THLS-32) were used to collect the data. A t-test, one-way analysis of variance, and Pearson correlation analysis were used to analyze the data. Results The majority (86.5%) of the parents used honey for their children's health problems. Among the parents, 83.1% utilized honey as a remedy for alleviating cough symptoms, 10.4% employed it as a treatment for diarrhea, and 14% administered it for the management of oral mucositis. The mean THLS-32 and HCAMQ scores of the parents were 29.39 and 21.31, respectively, and there was a moderate correlation between the parents' THLS-32 and HCAMQ mean scores (r = 0.662, p < 0.001). Conclusion This study revealed that a significant proportion of parents who used honey to alleviate their children's health issues displayed positive attitudes toward complementary and alternative medicine (CAM) while concurrently exhibiting insufficient or limited health literacy levels. Therefore, it is advisable to enhance health literacy regarding the proper and safe utilization of honey, which functions as a biologically based CAM therapy.